Tindak Tutur Ilokusi Asertif dan Direktif ILM Pandemi Covid-19 dalam Media YouTube - Lilis Muhlisoh; Sinta Rosalina; Dian Hartati (Jurnal Bahasa dan Sastra, 2022)
Public Service Advertisements (PSA) are one of the liaisons between the government and the community in disseminating information about the spread and prevention of the Covid-19 virus. This study aims to describe the types of assertive and directive illocutionary speech acts in public service advertisements on YouTube. In this research, the method used is descriptive qualitative method. The data collection technique in this study used the listening technique, namely listening to seven PSA video shows with the Covid-19 pandemic theme randomly on the YouTube channel Direktorat Promkes dan PM Kemenkes RI . The instrument in this study is the researcher himself, assisted by a table of assertive and directive illocutionary speech acts instruments. The data analysis technique was carried out in several stages: 1) data identification, 2) data classification and, 3) data description. The results showed that there were 10 utterances including assertive illocutionary speech acts with the types of informing, explaining, interpreting, and telling and 14 utterances of directive illocutionary speech acts with the types of prohibiting, ordering, inviting, obliging, suggesting, and warning.